Interchange : - Richards, Jack C. (Cambridge University Press, 2013)
Student's Book, Level 1 builds on the foundations established in the Intro level for accurate and fluent communication, extending grammatical, lexical, and functional skills. The Student's Book contains 16 teaching units, progress checks, additional Interchange activities, and a Grammar Plus section that provides additional grammar explanations and practice. Included is a Self-study DVD-ROM that provides the full class video and extra practice with vocabulary, grammar, speaking, listening, and reading.